Identification of a Novel Small RNA srvg23535 in Vibrio alginolyticus ZJ-T and Its Characterization With Phenotype MicroArray Technology - Deng, Yiqin; Su, Youlu; Liu, Songlin; Guo, Zhixun; Cheng, Changhong; Ma, Hongling; Wu, Jinjun; Feng, Juan; Chen, Chang (Frontiers in Microbiology, 2018)
Small non-coding RNAs (sRNAs) are important modulators of gene expression and are involved in the pathogenesis and survival of prokaryotes. However, few studies have been conducted with Vibrio alginolyticus, which limits our ability to probe the regulation of virulence and environmental adaptation by sRNAs in this opportunistic pathogen. In this study, the sRNA candidate srvg23535 was identified in V. alginolyticus ZJ-T. The precise transcript end, secondary structure, and sequence conservation were determined. A srvg23535 null mutant was constructed and characterized by using Phenotype MicroArray (PM) technology. In silico target prediction was conducted by IntaRNA and TargetRNA2. Subsequently, a 107 nt transcript was validated with a sigma70 promoter at the 5′ end and a Rho-independent terminator at the 3′ end. The sRNA srvg23535 had four stem-loop structures and was conserved among Vibrio harveyi, Vibrio parahaemolyticus, and Vibrio splendidus. Deletion of srvg23535 in V. alginolyticus ZJ-T led to a weaker utilization of D-mannose, D-melibiose, lactulose, and inosine as carbon sources but stronger utilization of L-cysteine as nitrogen source. Moreover, the srvg2353 mutant showed stronger resistance to osmotic stress but weaker resistance to pH stress. Additionally, a total of 22 common targets were identified and several were related to the observed phenotype of the mutant. This study indicated that the novel sRNA, srvg23535, is conserved and restricted to Vibrio spp., affecting the utilization of several carbon and nitrogen sources and the response to osmotic and pH stress. These results extend our understanding of sRNA regulation in V. alginolyticus and provide a significant resource for the further study of the precise target mRNAs of srvg23535, which may provide targets for antibacterial therapeutic or attenuated vaccines against Vibrio spp.